THE DEVELOPMENT OF MANAGEMENT MODEL PROGRAM OF VOCATIONAL SCHOOL TEACHER PARTNERSHIP WITH BUSINESS WORLD AND INDUSTRY WORD (DUDI) - Siswanto, Romi; Sugiono, Sugiono; Prasojo, Lantif Diat (Jurnal Ilmiah Peuradeun, 2018)
This study aims to: (1) formulate program management model and management model of vocational productive teacher partnership with DUDI; (2) evaluate model performance; (3) examine the effectiveness of collegial decentralization partner management models and formal centralization. This research uses R and D method with the procedure (1) data and information gathering; (2) product design; (3) design validation; (3) trials; (5) implementation and; (6) dissemination. The trial of the partnership management model is 60 vocational teachers participating in the partnership program of 4 expert competencies. The trial subject was determined by cluster random sampling technique. The data on the implementation of partnership program is obtained from the facilitator's assessment which is then analyzed using One way Anova and Scheffe. The management model of Vocational School productive teacher partnership program with DUDI is formulated using 5 management functions namely planning, organizing, implementing, monitoring, and evaluating (POIME). The result of variance analysis obtained F 102,51 and sig 0,00 <0,05. Anova scheffe advanced test shows no difference in the results of two groups of teachers who apply formalized model of centralization.